KARAKTERISTIK LENDUTAN RAKET TENIS AKIBAT KONTAK DENGAN BOLA - Gatut Rubiono; Anas Mukhtar (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
The contact between ball and tennis racket is a collision phenomenon. The ball exerts a force on the racket which causes deflection. This study aims to obtain the deflection characteristics of a tennis racket due to ball contact. The research was conducted by experiment with Kinetic brand rackets. The racket is clamps on the grip. The ball used is Nassau brand with 0.058 kg of mass. Free fall is arranged 1, 2 and 3 meters heights, with 3 hitting points on racket string. The deflection measurement uses the pen method at 5 points on racket frame. Five points are arranged sequentially from the grip with 6 cm distance. Data collection was carried out with 3 repetitions to get average value. The deflection was measured using a caliper with 0.01 mm accuracy. The results show that the deflection has a linear characteristic and depends on the momentum of the ball